MERONCE ACTIVITIES AS A MEANS OF IMPROVING FINE MOTOR SKILLS IN EARLY CHILDREN - Warti, Warti; Wahyudi, Wahyudi (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2024)
One learning approach that can be used to improve the fine motor skills of young children is meronce activities. This research aims to improve fine motor skills in young children through bead stringing activities. This type of research is classroom action research carried out in two cycles using data collection instruments in the form of observation sheets. Data analysis refers to the reference for the development of children's fine motor skills with standards for the level of achievement of children's development. The research subjects were students of RA Al-Mabrur Klunggen Slogohimo, Wonogiri. This study found that 64% of children's fine motor skills were underdeveloped, 9% were as expected, and 27% were very good. After the Cycle I intervention, children's fine motor skills increased by 19% in the underdeveloped group, 45% in the predictive group, and 36% in the superior group. Cycle II shows that children's fine motor skills are increasing. 82% of the category developed very well, 18% of the category developed as expected, and there were no children who developed poorly. The research was stopped in the second cycle because the prerequisites for success had been met. Therefore, the activity of stringing beads seems to be able to improve fine motor skills in young children. This activity develops hand-eye coordination, finger strength, and finger flexibility.